2017
DOI: 10.18203/2320-6012.ijrms20171237
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bupivacaine with fentanyl and bupivacaine with butorphanol for brachial plexus block by axillary approach- a prospective, double blind, randomized study

Abstract: INTRODUCTIONSurgical stress and pain elicits a consistent and well defined metabolic response, involving release of neuroendocrine hormones and cytokines that leads to myriad of detrimental effects. Regional anesthesia effectively produces mitigation of nociception as it diminishes the intensity of afferent impulses reaching the spinal cord. Brachial plexus block by axillary approach is one the most popular and reliable technique to provide anesthesia for forearm and hand surgeries. Furthermore, central neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Subsequently, it reduces the possible adverse effects of opioids, such as respiratory depression, nausea, sedation, etc. [7][8][9]. Fentanyl is a powerful synthetic opioid with a potency of 50 to 100 times greater than morphine.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it reduces the possible adverse effects of opioids, such as respiratory depression, nausea, sedation, etc. [7][8][9]. Fentanyl is a powerful synthetic opioid with a potency of 50 to 100 times greater than morphine.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Dose range of 20 μg/kg has been used in various studies. [8] Some authors concluded that up to 2 mg doses has been associated with minimal side effects. [9] Besides, there is no study suggestive of any appropriate dose of butorphanol as an adjuvant in supraclavicular brachial plexus block.…”
Section: Introductionmentioning
confidence: 99%